2022
DOI: 10.1111/1749-4877.12630
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in the composition and functional profiles of gut microbiota reflect dietary changes in plateau pikas

Abstract: Seasonal variations in gut microbiota of small mammals and how they are influenced by environmental variables are relatively poorly understood. We sampled 162 wild plateau pikas (Ochotona curzoniae) in 4 seasons over 2 and a half years and recorded the air temperature, precipitation, and nutrient content in edible vegetation at the sampling site. After conducting 16S rRNA and shotgun metagenomic sequencing, we found that the highest alpha diversity, the relative abundance of Firmicutes, and the simplest co-occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
43
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 75 publications
2
43
1
Order By: Relevance
“…Hence, as mentioned earlier, only a few studies have focused on investigating seasonal variations of gut bacteria. Moreover, these studies have used non-obese animals and therefore the effects of seasonal variations under an obesogenic context has not been sufficiently investigated yet [ 24 , 25 , 27 , 40 ]. Therefore, we investigated the effect of different photoperiods on gut microbiota composition in both healthy and obese rats and how those changes correlated with parameters related to obesity development such as body weight gain and fat depots accumulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, as mentioned earlier, only a few studies have focused on investigating seasonal variations of gut bacteria. Moreover, these studies have used non-obese animals and therefore the effects of seasonal variations under an obesogenic context has not been sufficiently investigated yet [ 24 , 25 , 27 , 40 ]. Therefore, we investigated the effect of different photoperiods on gut microbiota composition in both healthy and obese rats and how those changes correlated with parameters related to obesity development such as body weight gain and fat depots accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that the relative abundance of certain bacteria differed for Siberian hamsters housed in long- versus short-day lengths [ 21 , 23 ]. In addition, seasonal variations in gut bacteria related to dietary changes were found in plateau pikas [ 24 ]. In another study in giant pandas, seasonal oscillations of gut microbiota and higher short chain fatty acid (SCFA) production in the shoot-eating season were observed [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] In this context, fluctuations in environmental cues, mainly driven by the length of the daylight phase, have been linked to changes in the gut microbiota. [22][23][24] In fact, a study carried out in Siberian hamsters revealed that the intestinal microbiota is responsive to changes in photoperiods. These changes in bacterial abundance were associated with elevated body and fat mass observed in animals housed under long summer-like day length (LD) conditions compared to animals housed under short winter-like day length (SD) conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al (2022) demonstrated that there were two gut microbial community types in wild plateau pikas (Ochotona curzoniae), which had different microbial diversity, interactions, and functions. Fan et al (2022) also showed the composition and functional profiles of gut microbiota in plateau pikas varied among seasons, and environmental factors (especially diet) had profound effects on it. Yan et al (2022) found that freeliving wild camels (Camelus ferus) higher energy utilization efficiency compared to that of captive-living counterparts, therefore enable the host to adjust to a relatively barren field environment.…”
Section: Discussionmentioning
confidence: 96%